2017
DOI: 10.1016/j.jhep.2016.09.023
|View full text |Cite
|
Sign up to set email alerts
|

The association between sarcopenia and non-alcoholic fatty liver disease

Abstract: is a MD/clinical virologist and expert in hepatitis E, participated in the treatment team and made the figure. Prof. Arnon Kater, MD/hematologist, participated in the treatment team. Dr. Janke Schinkel, MD/clinical virologist and expert in hepatitis C, participated in the treatment team and suggested sofosbuvir as a potential compound to treat chronic hepatitis E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Sarcopenia has become an important concept for understanding the impact of aging on health outcomes. This condition is not only a physiological symptom of aging, but there is growing evidence that low muscle mass is a condition associated with a number of disorders [11][12][13][14][15][16][17]. Sarcopenia is common in elderly populations and contributes to functional limitations, disabilities, and frailty [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarcopenia has become an important concept for understanding the impact of aging on health outcomes. This condition is not only a physiological symptom of aging, but there is growing evidence that low muscle mass is a condition associated with a number of disorders [11][12][13][14][15][16][17]. Sarcopenia is common in elderly populations and contributes to functional limitations, disabilities, and frailty [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is common in elderly populations and contributes to functional limitations, disabilities, and frailty [18,19]. Furthermore, several previous studies have found an association with increased risk for several disorders, such as cardiovascular disease, metabolic syndrome, and morbidity or mortality, in individuals with sarcopenia [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia has become an important concept for understanding the impact of aging on health outcomes. This condition is a physiological symptom of aging, and there is growing evidence that low muscle mass is associated with a number of disorders . Sarcopenia is common in elderly populations and contributes to functional limitations, disabilities, and frailty .…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is a pathological condition characterized by the progressive loss of muscle mass and increased amount of visceral fat, despite a relatively constant bodyweight . Recent studies have shown that sarcopenia is associated with several diseases, as well as with poor morbidity and mortality outcomes . The pathophysiological backgrounds of sarcopenia, such as accumulation of visceral fat, metabolic abnormalities, and decreased physical activity, are similar to those of colorectal neoplasia.…”
Section: Introductionmentioning
confidence: 99%